VD_FINDINFO Décision / 2012 / 869 vom 29. März 2012 - VD Tribunal cantonal (2012)
RISQUE DE FUITE, RISQUE DE RÉCIDIVE, PROPORTIONNALITÉ, DÉTENTION PRÉVENTIVE | 212 al. 3 CPP (CH), 221 al. 1 let. a CPP (CH), 221 al. 1 let. c CPP (CH), 393 al. 1 let. c CPP (CH)